Comeasurement of simian virus 40 early and late promoter activity in HeLa and 293 cells in the presence of T antigen. - Kelly, J J (1989)
Transcription of the simian virus 40 (SV40) late promoter is strongly activated by SV40 T antigen. We were interested in examining this process in relation to other T-antigen functions such as replication and repression of early transcription. To quantitate the various T-antigen effects, we used a vector which has a promoterless beta-globin gene flanking the early and late sides of the SV40 promoter region. Following cotransfection with a plasmid encoding T antigen, transcription from the two promoters can be measured with a single S1 mapping probe and replication can be assayed by Southern blot analysis of DNA recovered in Hirt extracts. In this study, transactivation was examined in HeLa and 293 cells, since these cells differ in their ability to support SV40 replication. The strength of the late promoter relative to the early promoter was approximately three- to fourfold higher in 293 cells. Replication in 293 cells was also more efficient, by the same margin. In both cell lines, late promoter transactivation was barely detectable on replication-defective templates. Taken together, the results suggest that T-antigen activation of late transcription occurs only on replicated, or replicating, DNA. T antigen also activated the late-early start sites, and while in HeLa cells they were seen to be only 30% as strong as the late promoter, in 293 cells late and late-early activities were almost equal.